PROHNOSTYCHNIST AS PART OF INNOVATIVE EDUCATIONAL TECHNOLOGIES - Andrievsky, Б.М. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with mechanisms of prognostic modern educational technologies. Characterizes the prediction methods of educational institutions of education.